2013
DOI: 10.1007/s11695-013-0975-2
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Turnover Is Increased in the Excluded Stomach Mucosa After Roux-en-Y Gastric Bypass for Morbid Obesity

Abstract: Cell proliferation is increased and apoptosis is downregulated in the excluded gastric mucosa compared to the non-operated obese controls. Alterations in cell turnover and in hormonal secretions in these conditions may be of relevance in long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
10
0
3
Order By: Relevance
“…It has been reported that gastrin expression in the epithelium of the excluded stomach is modified after Roux-en-Y bypass, as shown after gastroduodenal exclusion, which could influence the proliferation of EC cells. Our observations demonstrate that cell modifications are not strictly related to the surgery, because they can be present before surgery [9].…”
Section: Discussionmentioning
confidence: 72%
“…It has been reported that gastrin expression in the epithelium of the excluded stomach is modified after Roux-en-Y bypass, as shown after gastroduodenal exclusion, which could influence the proliferation of EC cells. Our observations demonstrate that cell modifications are not strictly related to the surgery, because they can be present before surgery [9].…”
Section: Discussionmentioning
confidence: 72%
“…In our investigation, the proliferative index of epithelial cells through Ki-67 antigen expression increased in the postoperative period (23.8%) when compared to the preoperative (17.1%), mainly in cases with H. pylori presence. Safatle-Ribeiro et al (23) , observed a different result: gastric pouch cell proliferation was of 18.3% (the authors mentioned a treatment for pathogen eradication, but presented no cure confirmation). This result discrepancy could be explained by the higher postoperative H. pylori infection rate we found in our study, mainly in patients with greater period of postoperative follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…Safatle-Ribeiro et al (23) evaluated 35 patients submitted to RYGB with a postoperative follow-up higher than 36 months and observed Ki-67 antigen expression in the gastric pouch and in the excluded stomach mucosa. They compared these results to the expression of this antigen in the gastric antrum and body of not operated obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…RYGB causes hyperplasia of the jejunal mucosa of the Roux-limb, but no macroscopic or histologic evidence of inflammation is found in the majority of patients [14, 22]. An increased inflammatory state can be found in the stomach remnant, and more than half of the patients have chronic gastritis in this remnant [2325]. However, studies in non-RYGB patients with gastritis found no increase in fecal calprotectin [26].…”
Section: Discussionmentioning
confidence: 99%